Kontribusi Teori Pengondisian Klasik Terhadap Pengenalan Makharijul Huruf Hijaiyah Pada Anak Usia 5-6 Tahun - Wartini, Atik; Nurjannah (Institut Agama Islam Negeri Madura, 2024)
The Classical conditioning theory discovered by Petrovich Ivan Pavlov made an extraordinary contribution to the realm of early childhood education. This theory was discovered accidentally by Pavlov while conducting experiments to determine the digestive system of dogs. This theory is known for conditioned reflexes. This theory views that learning is a change in behavior. Classical conditioning theory is usually used in early childhood education, such as changes in behavior, attitudes, ethics and habits. Furthermore, this study will see how the contribution of classical conditioning theory to the introduction of hijaiyah letters in makharijul in children aged five to six years. The objects in this study were girls ages 5-6 years whose speech was unclear. Furthermore, this research will look at the contribution of classical conditioning theory to the introduction of makharijul hijaiyah letters. This research is a type of qualitative research in the from of research (field research), with a phenomenological approach using Creswell model. The results obtained, in children aged five to six years with cedal indications, that classical conditioning theory can contribute, children can recognize and pronounce hijaiyah letters correctly.